2012
DOI: 10.3758/s13421-012-0234-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of study time and meaningfulness on environmental context-dependent recognition

Abstract: In two experiments, we examined whether the size of place-context-dependent recognition decreased with study time and with the meaningfulness of the to-beremembered materials. A group of 80 undergraduates intentionally studied a list of words in a short (1.5 s per item) or a long (4.0 s per item) study-time condition (Exp. 1). Another 40 undergraduates studied lists consisting of words and nonwords in the long-study-time condition (Exp. 2). After a short retention interval, recognition for the targets was test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
(115 reference statements)
1
9
0
Order By: Relevance
“…Accordingly, the overshadowing principle predicts that the probability of CE will decrease with longer study time. Isarida et al (2012) clearly confirmed these predictions in two empirical experiments. Significant CEs were found in the short study-time condition (1500 milliseconds) but not in the long study-time experiment (4000 milliseconds).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Accordingly, the overshadowing principle predicts that the probability of CE will decrease with longer study time. Isarida et al (2012) clearly confirmed these predictions in two empirical experiments. Significant CEs were found in the short study-time condition (1500 milliseconds) but not in the long study-time experiment (4000 milliseconds).…”
Section: Introductionsupporting
confidence: 76%
“…In such conditions an "overshadowing" process seemed to take place. In line with the overshadowing principle, the strength of item cues was found to increase with the length of study time, at the expense of context cues (see also Isarida et al, 2012).…”
Section: Discussionmentioning
confidence: 69%
“…Environmental context-dependent recognition was once thought to be non-existent [ 3 ] but more recently several studies have found evidence for it and delineated some of the circumstances under which it occurs (e.g. [ 4 ]).…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for centuries that the presence of the learning event’s context at the moment of recollection greatly improves recall performance 1 4 . However, the scientific results regarding the effect of context on recognition are far from clear 4 , 5 . A range of experimental studies found no or weak contextual effects in face recognition experiments 6 8 .…”
Section: Introductionmentioning
confidence: 99%
“…They also revealed a large effect size with a retention interval of one day or more, and most interestingly, there were no differences in the effect sizes between recall and recognition. It is important to emphasize that the experiments reporting context effects in recognition memory decisions used mainly intentional learning paradigms 5 . In these situations, the subjects know that they need to memorize the information they have just seen or heard during learning, so the contextual information can be used as a cue already in the encoding phase and later in the recognition phase.…”
Section: Introductionmentioning
confidence: 99%